A unified analysis of four cosmic shear surveys. Issue 3 (27th October 2018) - Chang, Chihway; Wang, Michael; Dodelson, Scott; Eifler, Tim; Heymans, Catherine; Jarvis, Michael; Jee, M James; Joudaki, Shahab; Krause, Elisabeth; Malz, Alex; Mandelbaum, Rachel; Mohammed, Irshad; et al.
Abstract: In the past few years, several independent collaborations have presented cosmological constraints from tomographic cosmic shear analyses. These analyses differ in many aspects: the data sets, the shear and photometric redshift estimation algorithms, the theory model assumptions, and the inference pipelines. To assess the robustness of the existing cosmic shear results, we present in this paper a unified analysis of four of the recent cosmic shear surveys: the Deep Lens Survey (DLS), the Canada–France–Hawaii Telescope Lensing Survey (CFHTLenS), the Science Verification data from the Dark Energy Survey (DES-SV), and the 450 deg 2 release of the Kilo-Degree Survey (KiDS-450). By using a unified pipeline, we show how the cosmological constraints are sensitive to the various details of the pipeline. We identify several analysis choices that can shift the cosmological constraints by a significant fraction of the uncertainties. For our fiducial analysis choice, considering a Gaussian covariance, conservative scale cuts, assuming no baryonic feedback contamination, identical cosmological parameter priors and intrinsic alignment treatments, we find the constraints (mean, 16 per cent and 84 per cent confidence intervals) on the parameter S 8 ≡ σ8 (Ωm /0.3) 0.5 to beS_8=0.942_-0.045^+0.046 (DLS), 0.657_-0.070^+0.071 (CFHTLenS), 0.844_-0.061^+0.062 (DES-SV), and0.755_-0.049^+0.048 (KiDS-450). From the goodness-of-fit and the Bayesian evidence ratio, we determine that amongst the four surveys, the two more recent surveys, DES-SV and KiDS-450, have acceptable goodness of fit and are consistent with each other. The combined constraints areS_8=0.790^+0.042_-0.041, which is in good agreement with the first year of DES cosmic shear results and recent CMB constraints from the Planck satellite.